2017
DOI: 10.1007/s00170-017-1016-4
|View full text |Cite
|
Sign up to set email alerts
|

Friction stir consolidation of aluminum machining chips

Abstract: Conventional twist drilling is a widely used machining process for creating holes in aerospace and automobile structures. Drilling at room temperature can sometime affect the quality of machined holes due to increased thermal effects on the workpiece. Thermal effects can be a cumbersome when machining composites and fiber metal laminates due to their different thermal expansion coefficients, which may introduce additional stress in the structure. Thermal machining effects can be minimized using coolants suppli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…SPD processes commonly used for SSR are: Equal channel angular pressing (ECAP) [12,13], cyclic extrusion compression (CEC) [14], and high pressure torsion (HPT) [15]. Lately, new and promising methods for SSR are arising such as friction stir extrusion (FSE) [16] and friction stir consolidation (FSC) [17]. Tang et al [16] utilized FSE to produce aluminum AW 2050 and AW 2195 defect free wires from the machining chips, with good combination of the microhardness and bend ductility.…”
mentioning
confidence: 99%
“…SPD processes commonly used for SSR are: Equal channel angular pressing (ECAP) [12,13], cyclic extrusion compression (CEC) [14], and high pressure torsion (HPT) [15]. Lately, new and promising methods for SSR are arising such as friction stir extrusion (FSE) [16] and friction stir consolidation (FSC) [17]. Tang et al [16] utilized FSE to produce aluminum AW 2050 and AW 2195 defect free wires from the machining chips, with good combination of the microhardness and bend ductility.…”
mentioning
confidence: 99%
“…The non-homogeneous mechanical properties of consolidated billet during single-step FSC of aluminum alloy AA6061 were first reported by Li et al [36]. They found that the main reason for inhomogeneity was different plastic deformation and the temperature of the material in the radial direction and the advancing direction of the die.…”
Section: Introductionmentioning
confidence: 90%
“…AA5052 alloy is a common aluminum alloy with medium strength and usually used in a wide variety of structures like in boat hulls, gangplanks, and other products exposed to marine environments [11]. Machining chips with uniform size as precursors and desired thickness were collected by dry milling of the solid block metal using a milling machine model of FU281, and Equation 1 [13] was used to determine the desired chip thickness from initial 8mm diameter solid block.…”
Section: Methodsmentioning
confidence: 99%